Configurationally Stable Atropisomeric Acridinium Fluorophores - Fischer, Christian; Sparr, Christof (Synlett, 2018)
Arylated heterocyclic fluorophores are particularly useful scaffolds for numerous applications, such as bioimaging or synthetic photochemistry. While variation of the substitution pattern at the heterocycle and aryl groups allows dye modulation, the bond rotational barriers are also strongly affected. Unsymmetrically substituted ring systems of rotationally restricted arylated heterocycles therefore lead to configurationally stable atropisomeric fluorophores. Herein, we describe these characteristics by determining the properties and configurational stability of atropisomeric, tri-ortho-substituted naphthyl-acridinium fluorophores. A significant barrier to rotation of >120 kJ mol–1 was measured, which renders these dyes and related compounds distinct atropisomers with stereoisomer-specific properties over a broad temperature range.
Keywords: atropisomerism; heterocycles; fluorophores; acridinium salts; barrier to rotation